Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So here's the problem:

Find the slope of the tangent line of : $2(x^2 +y^2)^2 = 25(x^2 - y^2)$ at the point (3,1)

Cool: So here's what I did:

Simplification step: $2(x^2 +y^2)^2 = 25(x^2 - y^2) \Rightarrow 2(x^2+y^2)^2 = 25x^2 - 25y^2$

Differentiate both sides: $4(x^2 +y^2)(2x(x') + 2y(y')) = 50x(x') - 50y(y')$

Simplify:

$(4x^2 + 4y^2)(2x + 2y(y'))= 50x - 50y(y')$

$(4x^2 + 4y^2)(2x + 2y(y'))= 50x - 50y(y')$

$8x^3 + 8x^2y(y') + 8xy^2 + 8y^3(y')= 50x - 50y(y')$

$8x^2y(y') + 8y^3(y') + 50y(y') = 50x - 8x^3 + 8xy^2$

$(y') (8x^2y + 8y^3 + 50y) = 50x - 8x^3 + 8xy^2$

$y' = \frac{50x - 8x^3 + 8xy^2}{8x^2y + 8y^3 + 50y}$

Cool, got y'...

Now, should I take the original equation and solve for y and substitute? I'm not even going to try putting down my steps on here.

The prompt is to find m=?

Someone please help?

share|improve this question
4  
Just plug in the given $x,y$. It is better not to simplify. Differentiate immediately. Also, I wouldn't bother solving for general $y'$. As soon as you have differentiated, substitute. Then solve. –  André Nicolas Oct 3 '13 at 2:43
    
as André suggests, you have $x=3$, you have $y=1$. So in your formula for $y'$ you can "Plug and chug" –  Rustyn Oct 3 '13 at 2:44

3 Answers 3

up vote 2 down vote accepted

We start from $$2(x^2+y^2)^2=25(x^2-y^2).$$ Don't hesitate, Differentiate. We get $$4(x^2+y^2)(2x+2yy')=50x-50yy'.$$ Substitute $x=3$, $y=1$. We get $$4(10)(6+2m)=150-50m,$$ and therefore $130m=-90$.

share|improve this answer
    
the equation is actually $2(x^2 + y^2)^2 = 25(x^2 - y^2)$, but thank you! –  alvonellos Oct 3 '13 at 3:00
    
I bombed on my simplification, didn't I? –  alvonellos Oct 3 '13 at 3:01
    
Yes, I noticed that, minor modification. –  André Nicolas Oct 3 '13 at 3:01
    
Bombing on simplification happens a lot, at least to me. That's a very good reason not to do it if you don't have to. –  André Nicolas Oct 3 '13 at 3:02
    
Thank you so much –  alvonellos Oct 3 '13 at 3:03

$$y' = \frac{50x - 8x^3 + 8xy^2}{8x^2y + 8y^3 + 50y}$$ Substitute $x=3,y=1$ $$y' = \frac{50(3) - 8(3)^3 + 8(3)(1)^2}{8(3)^2(1) + 8(1)^3 + 50(1)}$$ $$y' = \frac{150 - 216 + 24}{72 + 8 + 50}$$ $$y' = \frac{-42}{130}$$ $$y' = -\frac{21}{65}$$

The slope of the line which is tangent to $2(x^2 +y^2)^2 = 25(x^2 - y^2)$ passes through point $(3,1)$ is $-\frac{21}{65}$

share|improve this answer
    
It says that's wrong. –  alvonellos Oct 3 '13 at 2:54

The answers above were wrong since the equation is wrong. It should be the following - y1= 8(x^2+y^2)-50)x/-(8(x^2+y^2)+50)y Then you get the slope as -9/13.

share|improve this answer
    
Can you provide a reason for why you say that the answers are wrong? –  user61527 Oct 31 '13 at 22:07

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.